Analysis of the Effect of Hull Vane Lifting Force on Fast Vessel Resistance: Straight Hull Vane - Nafiri Muhammad Kautsar; I Ketut Suastika (WAVE: Jurnal Ilmiah Teknologi Maritim, 2023)
In previous studies by Saputra, the use of straight Hull Vane® increased ship's resistance. Based on hypothesis, this was caused by lifting force from Hull Vane® being too large, so that ship experienced bow trim. To reduce bow trim, smaller Hull Vane® was made including Hull Vane® with AR = 8.5, AR = 22.9 and AR = 28.94 with speeds which were 11 knots (Fn = 0.34), 17 knots (Fn = 0.53), 20 knots (Fn = 0.62) and 26 knots (Fn = 0.8). From simulation results, it was found that use of a straight Hull Vane® in every aspect ratio variation on vessel was only effective at 11 knots speed which could reduce ship's resistance up to 17%. For speeds above 11 knots, increased in aspect ratio can reduce resistance but resistance on ships with straight Hull Vane® was still greater than on ships without Hull Vane® because lift force by Hull Vane® at ship stern was still too large, so the bow of ship was more submerged than ship without Hull Vane®. This caused value of the wetted surface area (WSA) and value of hydrodynamic pressure more increased than ships without Hull Vane®, so value of ship's resistance also increased.